Modular Design of Interfaces in Nanostructures from Quasicrystalline Blocks - A. E. Madison; P. A. Madison; V. A. Moshnikov; A. V. Solomonov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Aperiodic order offers the possibility of creating new materials and structures with nonstandard properties. Active research is currently underway to obtain materials from non-atom building blocks, materials and elements based on aperiodic deterministic structures, photonic crystals and quasicrystals, and metamaterials. In the absence of natural analogues, the development of theoretical principles for the targeted rational design of their structures plays an important role. An important requirement consists in combining subunits and building blocks into a complex hierarchical nanostructure such that the local order would change only slightly when passing through interface regions. A possible solution to this problem is epitaxial matching between individual layers of the nanostructure. More complex structures are built on the principles of modular design. Previously, the principles of modular design have not been applied to quasicrystalline structures.Aim. Apply the general principles of modular design to hierarchical structures containing quasicrystalline blocks.Materials and methods. The structure of icosahedral quasicrystals was studied by computer simulation within the unit cell concept. The modular design of interfaces was based on the preliminary construction of a 3D icosahedral packing followed by cutting out those 2D fragments that intersect along common chains of equivalent nodes. The layers cut from quasicrystalline packings perpendicular to the symmetry axes of the icosahedron contain structurally similar fragments of identical subunits, separated by alternating long and short spaces in accordance with the LS Fibonacci sequence. Projection of icosahedral structure elements onto a kinked surface provides a coherent cross-linking of fragments with different symmetries by using the modular design of nanostructures from quasicrystalline blocks.Results. The possibility of coherent cross-linking of fragments with different symmetries, which appears to be incompatible from the standpoint of classical theory, using the modular design of nanostructures from quasicrystalline blocks is confirmed.Conclusion. Examples of cross-linking of alternating layers with 2, 3, and 5-fold symmetries into a single hierarchical nanostructure without a significant violation of the local order when passing through interface regions are presented.